2023
DOI: 10.1111/jnc.15811
|View full text |Cite
|
Sign up to set email alerts
|

Milestone Review: Metabolic dynamics of glutamate and GABA mediated neurotransmission — The essential roles of astrocytes

Abstract: Since it was first generally accepted that the two amino acids glutamate and GABA act as principal neurotransmitters, several landmark discoveries relating to this function have been uncovered. Synaptic homeostasis of these two transmitters involves several cell types working in close collaboration and is facilitated by specialized cellular processes. Notably, glutamate and GABA are extensively recycled between neurons and astrocytes in a process known as the glutamate/GABA-glutamine cycle, which is essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 437 publications
(627 reference statements)
0
21
0
Order By: Relevance
“…GAT3 activities influence various astrocytic functions encompassing the regulation of inhibitory synapse efficacy, excitatory neurotransmission, and astrocyte synaptic proximity, underscoring the role of GAT3 as a key glial GABA transporter [65,66]. Interestingly, the genetic ablation of GAT3 is lethal in mice, suggesting its critical role in GABA homeostasis during early embryogenesis and development [67].…”
Section: Astrocytic Regulation Of Gaba In the Cnsmentioning
confidence: 99%
See 2 more Smart Citations
“…GAT3 activities influence various astrocytic functions encompassing the regulation of inhibitory synapse efficacy, excitatory neurotransmission, and astrocyte synaptic proximity, underscoring the role of GAT3 as a key glial GABA transporter [65,66]. Interestingly, the genetic ablation of GAT3 is lethal in mice, suggesting its critical role in GABA homeostasis during early embryogenesis and development [67].…”
Section: Astrocytic Regulation Of Gaba In the Cnsmentioning
confidence: 99%
“…The GABA taken up by astrocytes via GABA transporters is either recycled into the GABA/glutamine cycle, which plays critical roles in GABA metabolism between neurons and astrocytes (Figure 2), or metabolized within mitochondria by the GABA transaminase (GABA-T) enzyme, which is present in both neurons and astrocytes [53,70]. Importantly, research has demonstrated that almost half of the released GABA is taken up and metabolized by astrocytes, underscoring their role in regulating GABA levels in the CNS [67]. Therefore, it is evident that astrocytes are considered essential cells in maintaining GABA homeostasis in the brain.…”
Section: Astrocytic Regulation Of Gaba In the Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…This synthesis pathway, mediated by the enzyme (GAD), results in the production of GABA, which plays a crucial role in regulating neuronal excitability and the overall stability of the neural network. Furthermore, glutaminase and glutamine synthetase play crucial functions in glutamic acid, glutamine, and ammonia homeostasis in the brain, which is intimately connected to GABA biosynthesis (Andersen and Schousboe 2023 ).…”
Section: Gaba-producing Strains and Metabolic Pathwaymentioning
confidence: 99%
“…Historically, our understanding of these disorders was limited. However, with advancements in neuroscience and molecular biology, we have started to unravel the intricacies of their onset and progression [4]. Common neurodegenerative disorders include Alzheimer's disease, Parkinson's disease, Huntington's disease, and amyotrophic lateral sclerosis (ALS), among others.…”
Section: Introductionmentioning
confidence: 99%